2022
DOI: 10.3389/fpubh.2022.985188
|View full text |Cite
|
Sign up to set email alerts
|

The vicious cycle of the public's irrational use of antibiotics for upper respiratory tract infections: A mixed methods systematic review

Abstract: BackgroundThe public's irrational use of antibiotics for upper respiratory tract infections (URTIs) is prevalent worldwide. This study aims to synthesize evidence on how people use antibiotics to treat URTIs, its prevalence and determinants.MethodsA mixed methods systematic review was conducted using a convergent segregated approach. Relevant studies were searched from PubMed, Cochrane Library, Embase, and Web of Science. A qualitative analysis was initiated, exploring the public's antibiotic use experience fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 124 publications
0
12
0
Order By: Relevance
“…Such practice has been reported in patients as well. The source of this belief may stem from the fact that upper respiratory tract infections are often self-limiting; thus, the relief of symptoms while taking antibiotics is often interpreted as an indicator of their efficacy [ 20 ]. Disrupting this misconception requires interventions involving the participation of all stakeholders: patients, physicians, and pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…Such practice has been reported in patients as well. The source of this belief may stem from the fact that upper respiratory tract infections are often self-limiting; thus, the relief of symptoms while taking antibiotics is often interpreted as an indicator of their efficacy [ 20 ]. Disrupting this misconception requires interventions involving the participation of all stakeholders: patients, physicians, and pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…and their potential determinants (for details, please see publication elsewhere (18)). Briefly, to address RQ1, the CBM was used to depict the whole process of the public's behaviours regarding antibiotic use and served as indicators to identify the public's behavioural patterns through latent class analysis (LCA).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…To inform effective interventions, it is important to understand why people irrationally use antibiotics (18). Existing studies have shown that antibiotic use behaviours among the public include a variety of behaviours (18), such as information seeking, assessing alternatives, and antibiotics acquisition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics have been one of the most significant medical breakthroughs in modern medicine [ 1 ], enabling the treatment of complex medical conditions and saving millions of lives to date [ 2 ]. Antibiotic resistance is one of the most prominent threats to health systems and food security in the world [ 3 ], posing a major risk to human life and public health [ 4 ].…”
Section: Introductionmentioning
confidence: 99%